International mobility in apprenticeships: focus on long-term mobility : Germany - Huismann, Adrienne [Verfasser] (My University, 2020)
"Since 2005, the Vocational Training Act supports explicitly international mobility as part of the apprenticeship. National and regional targets have been set (10% of all IVET-learners shall have cross-country mobility experience by 2020). The National Agency at the Federal Institute for Vocational Education and Training (NA at BIBB) is implementing the Erasmus+ programme for VET, following the Leonardo da Vinci programmes. The NA at BIBB is also monitoring the overall international mobility of IVET-learners in Germany. On its behalf, two research studies were carried out on the status of mobility in 2010 and 2017, allowing to follow the consistent growth trend: while in 2010, approximately 17 000 IVET-learners had a stay abroad (mobility rate of 2.4%), more than 30 000 IVET-learners did so in 2017, reaching a new mobility record of 5.3% of all IVET-learners. Most stays abroad (over 85%) lasted up to one month. There were hardly any stays of over three months. So long-term mobility according to the EU definition (6 to 12 months) is really a niche phenomenon. Nonetheless, the aim of this article is to identify enablers and disablers of outgoing and in-coming (long term) mobility of apprentices in Germany at framework level (Chapter 1), system level (Chapter 2) and implementation level (Chapter 3)." (Author's text ; BIBB-Doku)
Keywords: G 1.3.3.3 Mobilität; 370; 330; Ausbildungsmobilität; Auslandsaufenthalt; Berufsbildungssystem; Nationale Agentur Bildung für Europa; Sprachkenntnisse; Erasmus plus; LEONARDO; Finanzierung